Proposed City-County Airport Agreement - Paul E. Wolven:::::: (1971)
A memorandum informing the Oxnard city council of the compromise proposal made between the Board of Supervisors and Oxnard City Council regarding the proposed airport. Includes an analysis of proposed airport agreements and a statement of policies regarding airports in Oxnard.